Orientasi Perilaku Kepemimpinan dalam Menciptakan Budaya Organisasi di Pondok Pesantren Hidayatul Mubtadi-ien Lirboyo Kediri - Abdul Kholiq; Ateg Ngalwan (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2022)
The role of leadership in creating a strong organizational culture is a series of processes from the entire organizational system that the process of forming organizational culture begins with the top leadership who seeks to implement the philosophy, vision and strategy of the organization. Leadership behavior will form a culture that is sustainable from year to year that provides real results for achieving organizational goals. The relationship between leadership and the organization is a social dimension of the organization which has recently become an interesting study. Leadership research emphasizes characteristics, behavior, power and influence, and situational approaches which are still one-way. The focus of the study in this research is the decision-making behavior in terms of disciplinary policies, management recruitment patterns and leadership behavior orientation tendencies in the Hidayatul Mubtadi-ien Islamic boarding school, Kediri. This type of research is aqualitative research with a composition of research design methods, presence of researchers, research locations, data sources, data collection procedures, data analysis, data validity checking, research stages. And the conclusion from this study is that decision-making behavior in the disciplinary policies of the Islamic boarding school Hidayatul Mubtadi-ien Lirboyo Kediri is based on provisions that already exist in Islamic boarding schools. While the pattern of recruitment of administrators at the Hidayatul Mubtadi-ien Lirboyo Kediri Islamic boarding school is carried out through registration, then selection or competency tests and decision making through a leadership meeting approved by the masyayikhs. while the tendency of leadership behavior at the Islamic boarding school Hidayatul Mubtadi-ien Lirboyo Kediri is oriented towards the relationship between administrators.